Cysteine/Penicillamine Ligation Independent of Terminal Steric Demands for Chemical Protein Synthesis. (20th May 2020) - Tan, Yi; Li, Jiasheng; Jin, Kang; Liu, Jiamei; Chen, Ziyong; Yang, Jun; Li, Xuechen
Abstract: The chemical ligation of two unprotected peptides to generate a natural peptidic linkage specifically at the C‐ and N‐termini is a desirable goal in chemical protein synthesis but is challenging because it demands high reactivity and selectivity (chemo‐, regio‐, and stereoselectivity). We report an operationally simple and highly effective chemical peptide ligation involving the ligation of peptides with C‐terminal salicylaldehyde esters to peptides with N‐terminal cysteine/penicillamine. The notable features of this method include its tolerance of steric hinderance from the side groups on either ligating terminus, thereby allowing flexible disconnection at sites that are otherwise difficult to functionalize. In addition, this method can be expanded to selective desulfurization and one‐pot ligation‐desulfurization reactions. The effectiveness of this method was demonstrated by the synthesis of VISTA (216‐311), PD‐1 (192‐288) and Eglin C. Abstract : That couple has great chemistry : A chemical ligation of peptides with C‐terminal salicylaldehyde esters to peptides with N‐terminal cysteine/penicillamine was developed. This method shows tolerance of steric hinderance from the side groups on either ligating terminus, thereby allowing flexible disconnection at sites that are otherwise difficult. This method can also be expanded to selective desulfurization and one‐pot ligation/desulfurization reactions.